Analysis of reading comprehension and disabilities among teenagers. - Martín-Ruiz, Isaías; González-Valenzuela, María José (Universidad de Murcia, 2022)
Evolutionary studies that analyse the development of reading comprehension and related difficulties among teenagers are relevant, given importance of this skill for academic performance at this age. The aim of this study is to analyse performance and difficulties in reading comprehen-sion and its components during adolescence. The sample is composed of 203 students aged 12 to 14, in the first, second, and third year of compul-sory Secondary Education from a randomly selected school in an average socio-cultural area of Malaga. Students are evaluated for reading compre-hension through the selection and organisation of textual ideas, as well as semantic and morpho-syntactic knowledge, after reading a descriptive text. Metacognition is assessed by means of a reading awareness questionnaire. The design is cross-sectional and observational, measuring five variables across three groups of students. A comparison of means and analysis of percentages of difficulties is carried out. The results show significant dif-ferences between the groups in the study variables, with the highest scores in the third year. Furthermore, between 15-30% of reading comprehension difficulties are found at these ages. The percentages are higher in the selec-tion and organisation of ideas across all three school years examined, and the percentages are higher in the third year for all the variables. These re-sults imply the need to control the teaching-learning processes of reading comprehension from an early age, in order to avoid difficulties in the first few years of secondary education.
Keywords: Comprensión lectora - Dificultades; Adolescentes - Lectura; Psicología de la lectura; Reading; Compulsory secondary education; Adolescents; Comprehension difficulties